2018
DOI: 10.5194/bg-15-2271-2018
|View full text |Cite
|
Sign up to set email alerts
|

Regional trends in the fractional solubility of Fe and other metals from North Atlantic aerosols (GEOTRACES cruises GA01 and GA03) following a two-stage leach

Abstract: Abstract. The fractional solubility of aerosol-derived trace elements deposited to the ocean surface is a key parameter of many marine biogeochemical models. Despite this, it is currently poorly constrained, in part due to the complex interplay between the various processes that govern the solubilisation of aerosol trace elements. In this study, we used a sequential two-stage leach to investigate the regional variability in fractional solubility of a suite of aerosol trace elements (Al, Ti, Fe, Mn, Co, Ni, Cu,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 82 publications
15
110
0
Order By: Relevance
“…Like Bridgestock et al (2016) found in the tropical Atlantic, we see evidence of a natural Pb source to the northern North Atlantic which was previously obscured in the 1980s and 1990s by enormous anthropogenic inputs, and which is still obscured in magnitude by the relatively greater solubility of anthropogenic-derived atmospheric Pb. Aerosol samples collected concurrently with our seawater samples support our determination that Pb in the surface waters is partially of natural origin (Shelley et al, 2017(Shelley et al, , 2018, and work by Prospero et al (2012) introduces the possibility that much of the dust in the Irminger Sea and Iceland Basin is actually from high-latitude sources such as Icelandic dust. Future work to better constrain end-members could validate this hypothesis.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Like Bridgestock et al (2016) found in the tropical Atlantic, we see evidence of a natural Pb source to the northern North Atlantic which was previously obscured in the 1980s and 1990s by enormous anthropogenic inputs, and which is still obscured in magnitude by the relatively greater solubility of anthropogenic-derived atmospheric Pb. Aerosol samples collected concurrently with our seawater samples support our determination that Pb in the surface waters is partially of natural origin (Shelley et al, 2017(Shelley et al, , 2018, and work by Prospero et al (2012) introduces the possibility that much of the dust in the Irminger Sea and Iceland Basin is actually from high-latitude sources such as Icelandic dust. Future work to better constrain end-members could validate this hypothesis.…”
Section: Discussionsupporting
confidence: 70%
“…Although dust deposition to the North Atlantic Ocean is typically associated with northern African dust from the Sahara, Prospero et al (2012) and Bullard et al (2016) found that high-latitude dust emissions, specifically volcanic-based soils from Iceland, could be substantial enough to impact oceanic Fe cycling; therefore we suggest that the elevated Pb in the nearsurface waters of the Iceland Basin and Irminger Sea may possibly be dust-derived. In the GEOVIDE shipboard aerosol data (Shelley et al, 2017(Shelley et al, , 2018, Pb concentrations were high in the Iceland Basin but low in the Irminger Sea. However, as Pb has a residence time of ∼ 1 year in this region, seasonal changes in the flux also could account for this difference.…”
Section: Near-surface Oceanmentioning
confidence: 96%
See 3 more Smart Citations